Severe case of COVID −19 pneumonia complicated by SIADH. (January 2022) - Fajri, Mohamed; Essafti, Meryem; Aloua, Rachid; Mouaffak, Youssef
Abstract: Introduction: Hyponatremia is one of the most common water–electrolyte imbalances in the human organism. This disorder is usually secondary to various diseases, including infections. The syndrome of inappropriate secretion of antidiuretic hormone (SIADH) is among causes of hyponatremia in critical care. It can be induced by a variety of conditions, including atypical lung disease. Discussion: The COVID-19 infection is associated with multiples metabolic disorders. However, hyponatremia associated with SIADH and Coronavirus disease 2019 (COVID-19) is not a usual clinical situation, but it was recently mentioned in a few case reports. Conclusion: We discuss a unique case of an acute symptomatic hyponatremia and SIADH, attributed to COVID-19. Highlights: The COVID-19 infection is associated with multiples metabolic disorders. Hyponatremia is one of the most common water–electrolyte imbalances in the human organism. It is usually secondary to various diseases. The syndrome of inappropriate secretion of antidiuretic hormone is among causes of hyponatremia in critical care.